2018
DOI: 10.1590/abd1806-4841.20186640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dermatoses in patients referred for evaluation in an outpatient clinic of specialties

Abstract: BackgroundBrazilian Unified Health System presents a long waiting period for a dermatology appointment, varying from 34 to 239 days.ObjectivesAnalyze the prevalence of cutaneous diseases evaluated by dermatologists in a specialized center, in patients referred from the primary care, and to present possible interventions for the primary units.MethodsRetrospective analyses of the International Codes of Diseases (ICD-10) described in every dermatology appointment in a specialty center in Sao Paulo from January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…One study in a public Brazilian secondary care center showed acne as the fourth most frequent complaint in dermatologists' office. 7 We found that 2/3 of the patients were not referred to an in-person dermatologist. Instead, their general practitioners received diagnosis and treatment from the teledermatologist to manage the patients.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…One study in a public Brazilian secondary care center showed acne as the fourth most frequent complaint in dermatologists' office. 7 We found that 2/3 of the patients were not referred to an in-person dermatologist. Instead, their general practitioners received diagnosis and treatment from the teledermatologist to manage the patients.…”
Section: Discussionmentioning
confidence: 74%
“…One study in a public Brazilian secondary care center showed acne as the fourth most frequent complaint in dermatologists’ office. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Ressalta-se que há uma ausência de estudos e prevalência, principalmente em serviços de atenção secundária à saúde, o que dificulta ações destinadas ao manejo efetivo das dermatoses. Além disso, as pesquisas epidemiológicas a respeito das dermatoses mais frequentes no país são limitadas à abrangência geográfica e demográfica (CARVALHO MTF, et al, 2008;AVANCINI J, et al, 2018).…”
Section: Introductionunclassified
“…Portanto, ainda há questões que precisam ser respondidas, entre elas, os principais sinais e sintomas apresentados pelos pacientes e que caracterizam uma síndrome mão-pé; e as estratégias de tratamentos propostos cujos mecanismos propiciam bons resultados tanto na prevenção quanto no tratamento, assim como a relação da síndrome mão-pé com onicomicoses 10 .…”
Section: Introductionunclassified